Induction Motor Hybrid Coordinate Transformation Model and Its Application - LIANG Yan-ping; WAN Yin-long; WANG Chen-guang (Journal of Harbin University of Science and Technology)
For the strong coupling problem between the rotor current and the air gap flux in the expression of the electromagnetic torque expression of the induction motor，the hybrid coordinate transformation is adopted by the αβ0 transformation and the MT0 transformation，and the electromagnetic torque expression of the induction motor is decoupled． The hybrid coordinate transformation is deduced，and the mathematical model of hybrid coordinate transformation of induction motor is given． The simulation model of the induction motor is respectively established under the hybrid coordinate system and the ABC coordinate system． The mathematical model of the hybrid coordinate transformation in the induction motor is verified by comparing the simulation results． In the application of the hybrid coordinate transformation，the indirect vector control simulation system based on flux linkage open-loop and speed closed loop is taken as an example． The simulation results show that the stator current of the induction motor is decoupled into the stator current component generating the magnetic field and the stator current component generating torque by the hybrid coordinate transformation，so the validity of the hybrid coordinate transformation is verified．